PENANGGULANGAN KEBAKARAN LAHAN DI DESA TANJUNG PERANAP KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Yulia Andriani; Rosnita Rosnita; Roza Yulida (Fakultas Pertanian, Universitas Riau, 2018)
Forest and community land fires are national disasters that often occur in Indonesia. These forestand land fires are actually the problem inherited from peat management in the past. Variety ofefforts have been conducted to overcome this land fire, both those carried out by the governmentand non-governmental organizations. Many things cause land fires, including economic, social andcultural factors of customs and traditions. For this reason, active participation from the communityis needed. This study aimed to identify activities or programs that have been and are being carriedout in controlling land fire in Tanjung Peranap Village, Tebing Tinggi Barat Subdistrict, KepulauanMeranti District, both carried out by non-governmental organizations and the government. By usingin-depth interview method, it was found that several activities and programs for land firemanagement are establishing fire-caring communities (MPA), farming with intercropping methods,empowering idle land (as much as 200 ha) into productive agricultural land, pilots the project of thepeat restoration agency (BRG) and IPB, utilizing local wisdom namely abu uyung to open farmland.